2014
DOI: 10.1038/psp.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling Framework for Quantitative Prediction of an Herb–Drug Interaction

Abstract: Herb–drug interaction predictions remain challenging. Physiologically based pharmacokinetic (PBPK) modeling was used to improve prediction accuracy of potential herb–drug interactions using the semipurified milk thistle preparation, silibinin, as an exemplar herbal product. Interactions between silibinin constituents and the probe substrates warfarin (CYP2C9) and midazolam (CYP3A) were simulated. A low silibinin dose (160 mg/day × 14 days) was predicted to increase midazolam area under the curve (AUC) by 1%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 46 publications
(101 reference statements)
1
40
0
Order By: Relevance
“…This framework centers on the evaluation of isolated constituents to ascertain the relative contribution of each constituent to the mixture, as well as to identify marker constituents that can be used to predict the likelihood and magnitude of these interactions. As an extension of previous studies focused on cytochrome P450-mediated inhibition (Brantley et al, 2010(Brantley et al, , 2013(Brantley et al, , 2014bKim et al, 2011), this framework was applied to 13 isolated constituents and 2 extracts as inhibitors of glucuronidation with a focus on gut-relevant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This framework centers on the evaluation of isolated constituents to ascertain the relative contribution of each constituent to the mixture, as well as to identify marker constituents that can be used to predict the likelihood and magnitude of these interactions. As an extension of previous studies focused on cytochrome P450-mediated inhibition (Brantley et al, 2010(Brantley et al, , 2013(Brantley et al, , 2014bKim et al, 2011), this framework was applied to 13 isolated constituents and 2 extracts as inhibitors of glucuronidation with a focus on gut-relevant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibition potency toward 4-MU glucuronidation may not be predictive of the effects on enteric glucuronidation of clinically relevant substrates (Dong et al, 2012;Chengcheng et al, 2013), these dietary substances could be evaluated further as inhibitors of the glucuronidation of such substrates, including ezetimibe, MPA, and raloxifene, using a similar systematic approach. Results would prioritize for advanced modeling and simulation techniques that integrate in vitro inhibitory potency (K i ) with available clinical pharmacokinetic data to provide quantitative predictions of dietary substance-drug interaction risk (Brantley et al, 2014b). Modeling and simulation can be used to prioritize for clinical evaluation and to guide the design of clinical interaction studies, with the ultimate goal of providing conclusive evidence about the risk or safety of certain dietary substance-drug combinations.…”
Section: Diet-derived Inhibitors Of Intestinal Glucuronidation 1679mentioning
confidence: 99%
See 2 more Smart Citations
“…These observations combined with the high systemic silibinin concentrations suggested a potential warfarin-milk thistle interaction [43]. However, a proof-of-concept clinical study showed only minimal interaction between a high-dose of silibinin in combination with both midazolam (CYP3A and (S)-warfarin 9 and 13 % increase in AUC, respectively) [44].…”
Section: Silibininmentioning
confidence: 99%